2013
DOI: 10.1016/s1743-9191(13)60014-x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous monitoring of the recurrent laryngeal nerve in thyroid surgery: a critical appraisal

Abstract: RLN traction injury is still the most common cause of RLN injury and is difficult to avoid with the application of I-IONM in thyroid surgery. C-IONM is useful to prevent the imminent traction injury by detecting progressive decreases in electromyographic amplitude combined with progressive latency increases. C-IONM seems to be a technological improvement. Likely, C-IONM by vagal nerve stimulation should enhance the standardization process, RLN intraoperative information, documentation, protection, training, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 15 publications
2
40
0
1
Order By: Relevance
“…In recent years, a CIONM has been developed that employs repetitive vagal stimulation and provides continuous visual and acoustic feedback of nerve function to allow early phases of nerve injury to be immediately detected after possible injurious maneuver . In our previous animal study, we demonstrated that RLN traction injury showed graded partial EMG changes, and early release of the traction before EMG has degraded to LOS offers a good chance of EMG recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a CIONM has been developed that employs repetitive vagal stimulation and provides continuous visual and acoustic feedback of nerve function to allow early phases of nerve injury to be immediately detected after possible injurious maneuver . In our previous animal study, we demonstrated that RLN traction injury showed graded partial EMG changes, and early release of the traction before EMG has degraded to LOS offers a good chance of EMG recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The skilful use of CIONM requires experience and observation of the EMG screen to quickly respond to abnormal EMG signal and alarms (37). Meaningful warning thresholds need to be defined and implemented such that automated alarms are sounded and visually displayed once a critical EMG threshold is exceeded.…”
Section: Recognition Of Impending Nerve Injury By Continuous Neural Mmentioning
confidence: 99%
“…CIONM is thought to reduce permanent vocal fold palsy rates more effectively than IIONM (0% vs. 0.4%; P = .019) because it measures nerve electrophysiology more accurately, and continually verifies functional integrity of the vagus–RLN axis in real‐time. Altogether, CIOMN facilitates reversal of the injurious surgical maneuver associated with the electromyogram (EMG) alteration by alerting the surgeon to impending nerve injury …”
Section: Introductionmentioning
confidence: 99%